ANN and GIS-assisted methodology for wind resource assessment (WRA) in Sarawak - Lawan, S.M; Abidin, W.A.W.Z.; Lawan, A.M.; Mustapha, M.; Bichi, S.L. (Penerbit UTM Press, 2015)
Wind energy is a reliable, clean source and has emerged as one of the dependable, and the best performing developing renewable energy around the world. It has insignificant environmental impacts, compared to other energy sources. In Sarawak, Malaysia, wind resource varies depending on the location. An inadequate number of wind stations are the major obstacles that slow down the growing of green energy in the region. Site selection is a crucial issue for potential investors and policy makers. This paper examines the spatial distribution and the amount of potential wind power and energy densities for wind energy production and suitable locations in Sarawak. A geographical Information System (GIS) assisted methodology, which includes wind speed, power and energy densities using the existing wind station and based on the newly developed prediction model called topographical neural network (TNN) were used. Kriging interpolation was employed for a simple interpolation of data between locations. The results show that the northeast, northwest and coastal regions have better prospects of wind energy. The studied GIS methodology can be applied for identification of the most suitable locations for wind energy harvesting. The developed maps can further be used in micro-siting and economic evaluation analysi